Do Chinese government policies affect performance of real estate enterprises? - Zhang, Lihua; Xin, Yueji; Han, Rui; Zhang, Xili; Hao, Ning; Li, Lele; Zhang, Juanfeng (International Journal of Strategic Property Management, 2024)
The Chinese central government has instituted a series of macro-economic tightening and easing policy measures on the real estate industry to stabilize the housing market in recent decades. However, our understanding of these policies and their impact on real estate firms is limited. This paper constructs an index of government policies on the real estate industry by collecting national housing policies in China from 2007 to 2019. We use this index to quantify the impact of government policies on real estate enterprises’ performance, based on data from 103 real estate enterprises listed on the Chinese A-share market. Two important conclusions are drawn from the panel data regression. First, tightened real estate policies significantly lower real estate enterprises’ profitability (ROA and ROE), while increase their liquidity risk. Second, the heterogeneity analysis shows that the tightened real estate policies yield downward impact more mildly on state-owned real estate enterprises than non-state-owned enterprises.